The Effectiveness of Aqueous Propolis Extract in Reducing the Enterococcus faecalis Count in Primary Teeth: An In Vitro Study - Majd Refaay; MHD.Bashier Almonakel; Samar Alsalameh; Ibraheem Hawary; Yasser Alsayed Tolibah (International Journal of Dentistry)
Conclusion: In total, 11% aqueous propolis extract is antimicrobial against E. faecalis. However, its efficacy was less than 2.5% sodium hypochlorite.